A pronúncia no procedimento do Tribunal do Júri brasileiro - Iribure Júnior, Hamilton da Cunha (2009)
Procedural law complies with the task of regulating the exercise of judicial functions, a fundamental activity of Democratic State of Law. In the current constitutional order the Jury Court is recognized and upheld both as law and fundamental individual guarantee. It is perceived as a fundamental human right because people's participation in the trials made by the judiciary. It is the fundamental guarantee that the person who has committed an intentional criminal offense against life can only be condemned by the verdict issued by a People's Court. The jury is a province where there is the exercise of citizenship, revealing itself as a democratic right for the individual to be judged by a board of citizens. The Brazilian legal system provides the procedure of the Jury Court divided into stages. This scaling ensures that the formation of the prosecution of the defendant is given in two very different stages: a preliminary investigation and trial of the case. In the first phase, conducted by a judge, it is discussed the admissibility accusatory. In the trial of the case occurs the trial of the defendant by People´s Court. The judicial decision that examines and accepts the accusation against the defendant is called jury indictment, that terminating the preliminary investigation and forward the accused for trial in the Plenary of the Jury. The indictment has always been present in Brazilian history of criminal procedure, from the time of the Ordinations of the Kingdom. In most foreign jurisdictions is clear that there is a procedural institute with similar function that jury indictment exercises in Brazil. This judicial act represents an important mechanism to control the accusatory activity on the jury procedure to ensure that the cause is only being sent to the Jury if it is in strict conformity with the requirements established in law. Should the judge that decides the jury indictment works with extra caution in the grounds of this decision because this stage of the proceedings of the jury is not to examine the right to punish, but only the right to accuse. Therefore, the excess on the motivation of this judicial act can lead to anticipation of a merit´s judgment to an irregular stage of the process. The jury indictment, interlocutory decision in the proceedings of the jury, is the main object of analysis in this work. In establishing the Democratic State of Law, the Constitution of the Republic established in 1988 as one of its grounds human dignity, the rule that guides the interpreter in the applicability of the standards of the legal system. So this work is has the aim of examining the principles and procedures focused on the jury indictment in the light of that constitutional grounds as a way of being assured the due process of law